An international analysis of parental school preferences. - Jerrim, John; Prieto-Latorre, Claudia; López-Agudo, Luis Alejandro; Marcenaro-Gutiérrez, Óscar David (My University, 2023)
Parents are concerned about their children’s educational progress, and thus school choice has an important role in parenting. This research analyses the features when choosing a school in the countries participating in the Programme for International Students Assessment between 2009 and 2018. Specifically, this study seeks to understand whether there are variation in mothers and fathers school preferences related to school safety, school climate, reputation, finance and academic standards. Ordinal logistic regressions illustrate that mothers are more likely to indicate that a school environment is important when selecting a school compared to fathers. Specifically, this difference is larger in Western regions. In addition, we did not identify meaningful parental differences between sons and daughters. In light of these findings, it would be useful to collect data from both mother and father, particularly in the areas where their opinions are more likely to differ.
Keywords: Educación - Aspectos sociales; Familia y enseñanza; PISA; Mother vs father; School choice